2020
DOI: 10.5334/ijc.1011
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Analysis of the Benthic Fisheries Managed in the TURF System in Chile

Abstract: Territorial use rights in fisheries (TURF) are considered to aid to the sustainability of smallscale fisheries, because they remove the perverse incentives, which sustain the tragedy of the commons. Nevertheless, a comprehensive evaluation of the implementation of TURFs is lacking. Chile offers a unique opportunity, because an extensive system for benthic fisheries has been implemented, with at present hundreds of TURFs along the coast. This study analyzes the sustainability of all the TURFs (109) along a stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…This monitoring should include integral spatial management since all commercial species considered in MAs management plans have long dispersive larval stages hence settlement, recruitment and growth are processes that probably greatly exceed the boundaries of MAs (Romero et al, 2019). In short, the productivity of one area is dependent on processes and management in other OAAs and MAs (Molinet et al, 2010;Arias and Stotz, 2020). It should be highlighted that our results are the first attempt to evaluate MAs' performance in comparison with OAAs regime on a regional scale with a community approach in Aysén (43.9 • -45.2 • S).…”
Section: Implications For Management Of Fisheries and Benthic Environ...mentioning
confidence: 82%
See 1 more Smart Citation
“…This monitoring should include integral spatial management since all commercial species considered in MAs management plans have long dispersive larval stages hence settlement, recruitment and growth are processes that probably greatly exceed the boundaries of MAs (Romero et al, 2019). In short, the productivity of one area is dependent on processes and management in other OAAs and MAs (Molinet et al, 2010;Arias and Stotz, 2020). It should be highlighted that our results are the first attempt to evaluate MAs' performance in comparison with OAAs regime on a regional scale with a community approach in Aysén (43.9 • -45.2 • S).…”
Section: Implications For Management Of Fisheries and Benthic Environ...mentioning
confidence: 82%
“…Positive effects were also reported in the associated macroinvertebrate communities where higher species richness, biomass and densities were observed within MAs compared to OAAs (Gelcich et al, 2008, 2012, Biggs et al, 2016. In contrast, performances of MAs in northern Chile were classified as poorly sustainable, with few stocks showing stability in densities, sizes, and catches over time (Arias and Stotz, 2020). Moreover, to maintain productivity, studies showed that at least half of the catch was extracted from areas outside MAs (Gonzalez et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Their low profits are also affected by poaching (whether by outsiders, non-unionized fishers, or even by members). Poaching is one of the main factors influencing the scarcity of the target resource and one of the most critical problem perceived by fishers [ 77 , 79 , 81 , 106 , 127 , 128 ]. Thus, ignoring illegal activity outcomes in false conclusions (over- and under-representation) about the state and trends of fisheries; it also adds to the increased costs associated with surveillance and reduced income for fishers [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Management of the MEABRs is complex and fishers’ responses can have unforeseen consequences leading to failure. As stated earlier, many examples of the MEABR system are being applied with no consideration of the socio-ecological systems upon which they were implemented [ 59 , 61 , 65 , 79 ]. The lessons learned with the MEABR system in Chile could be helpful for the TURF system worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…This tendency has been also reported in Chile, where most of the surf clam AMERBs have historically failed at some point Stotz 2013, Aburto et al 2014) and where the Peñuelas A is an exception among the attempts to manage the resource under the AMERB regime. In this study, fishers identified factors based on their own experiences and knowledge that we classified as biophysical conditions of Coquimbo Bay, that seem to favor the presence of a relatively reliable stock, making this AMERB sustainable over time, unlike the other sandy beaches of the CBS or other beaches along the surf clam distribution range (Thiel et al 2007, Aburto et al 2014 or even compared with the rocky shore AMERB where 98% (n = 61) of the AMERBs in Coquimbo Region were considered unsustainable (70%) or poorly sustainable (28%) based on their productivity (Arias and Stotz 2020). In the case of the Peñuelas A, the interactions between institutions and the ecological attributes of this SES contribute to success of this fishery (Epstein et al 2015).…”
Section: The Peñuelas a Amerb Success Based On Fishers' Local Ecological Knowledgementioning
confidence: 99%